A novel experience of ultrasound-guided erector spinae plane block with sedation in breast cancer surgery: a case report - Alam, Tanveer; Qureshi, Rabeea Sajid; Mehdi, Syed Raza (Journal of the Pakistan Medical Association, 2023)
We are reporting the anesthetic management of a breast cancer patient with a high risk to undergo general anesthesia using a single shot ultrasound guided Erector Spinae Plane Block (ESPB) with monitored sedation. Targeted at T4, 20 mL of 0.375% Bupivacaine provided complete surgical anesthesia in 15 minutes. Concurrent sedation was administered with Target Controlled Infusion of Propofol with Entropy monitoring throughout the procedure. The surgery lasted 90 minutes and the patient remained pain free and hemodynamically stable throughout. At the end of the surgery, the patient received 1g Paracetamol intravenously, and did not require any further analgesics other than routinely administered Paracetamol until her discharge from the hospital. On top of the successful execution of our plan, this case was especially interesting as her postoperative analgesia remained completely opioid free. Keywords: Ultrasound, breast cancer, esp block, erector spinae plane block, fascial plane block, pain, analgesia, regional anesthesia.